Atma Reksa (Sebuah Refleksi tentang "Semangat Melayani" dalam "Atma Reksa") - Drs. Alexander Reba, M.Th (Atma Reksa : Jurnal Pastoral dan Kateketik, 2016)
Serving spirit has become the core spirit of SekolahTinggi Pastoral AtmaReksa (Stipar). The entire pulse of Stipar development from the beginning up to now never turns or even moves away from its duty to educate young servants for the church as well as for the nation. The challenges the servants often encounter in the field will never be able to minimize or weaken the serving spirit of Stipar institution to continue producing tough and talented catechists. The serving spirit flows out from ‘atmareksa’ is the pastoral spirit originated from Jesus Christ, the good Sheperd. Thisserving spirit is adopted to imitate Jesus Christ inrendering his service which had revolutionary changed the serving orientationin his time: Jesus practiced the down to earth spirit of serving which is really reached out the poor. By taking the option for the poor as his strategic choice in pastoral work, he effectively knocked down the upward-oriented serving practice as shown by Jewish leaders in his time. This serving spirit has become Stipar prime principal for the formation of the catechists, the lay apostles.